Study of interfacial design for direct-current tribovoltaic generators. (April 2022) - Xu, Xiyan; Li, Jun; Tao, Xinglin; Yan, Qi; Wu, Han; Guan, Zhengxin; Liu, Liqiang; Chen, Xiangyu; Ou-Yang, Wei
Abstract: As a newly discovered physical phenomenon, tribovoltaic effect has potential applications in various fields. Herein, we systematically study the relationship between interfacial properties of the tribovoltaic generator and its output performance using a conductor-semiconductor (C-S) structure. Based on several similar physical models, we derive an equation to quantify the effects of contact area, load force and the density of surface states of the semiconductor on performance of the tribovoltaic generator. The experimental results are in good agreements with the theoretical analysis. Moreover, the contribution of interfacial electric field and interfacial magnetic field to the tribovoltaic effect are discussed, respectively. By using epitaxial silicon (Si) film, the built-in electric field near the C-S interface can be regulated, which leads to suppression of the recombination effect of the tribovoltaic charges, and the short-circuit current of the tribovoltaic generator can be increased by 66.83%. This work paves the way for electrode design and better output performance of flexible DC tribovoltaic generator in the future. Graphical Abstract: ga1 Highlights: A series of impact parameters are studied for the tribovoltaic generators. A physical model is established for analyzing influence of interfacial properties. The output current is increased by 66.83% with a back surface field layer.